#boulietacks: Carpet tacks and mobile interfaces in the urban politics of cycling in Melbourne, Australia. Issue 3 (4th July 2017) - Chambers, Peter; Andrews, Thomas
Abstract : Since early 2014 small carpet tacks have been persistently dropped on an undulating stretch of road in Melbourne, Australia—ostensibly targeting road cyclists. No one knows where they come from. And yet the recurring presence of these rough-hewn iron nails continue to cause serious injury, property damage and nuisance to those who use this space, all the while flummoxing law enforcement and road maintenance authorities. Our aim in this paper is to follow the interfaces between tack and tyre, finger and phone, image and social media platform, to produce a detailed account of how these mediations are materialised and mobilised politically. Here, we use mobile interfaces to think through the complexity of embodied and deeply material uses of urban space as we narrate the ways in which groups become politically organised through various media. In this dispatch, we trace the development and deployment of a hashtag—#boulietacks—as a means of following this particular Antipodean enigma through the social media and digital communications platforms. Spread on roads and between living people in the city, tacks shape different kinds of political action in response to the anonymous and asymmetrical introduction of hazards into an urban environment customarily adopted for use in road cycling—the lifeless tacks mobilise a lively politics between urban modes of existence.